Efforts to reduce the risk of anterior cruciate ligament injury through isometric quadriceps exercise - Astiti Suadnyana, Ida Ayu; Novianti, I Gusti Ayu Sri Wahyuni; Thanaya, Sayu Aryantari Putri; Suharsono, Agung; Setiawan, Edi (UIR Press, 2022)
Anterior cruciate ligament (ACL) injury is one of the most common musculoskeletal injuries in the knee joint. One of the treatments for this injury is reconstruction. Pain is one of the most frequent problems that occur following reconstruction. Isometric quadriceps exercise can be given to reduce pain after phase I reconstruction in patients with ACL injuries. This study was a pre-experimental study with a one group pre and post-test design. This study was conducted in the outpatient room of Bali Royal Hospital Denpasar from March to May 2022. The subjects of this study were 20 patients with ACL injury following phase I reconstruction at Bali Royal Hospital, who met the eligibility criteria of this study. The quadriceps isometric exercise was performed 3 times a week for 4 weeks. Pain was measured using the visual analogue scale (VAS). In this study, the average pain score before and after exercise was 6 ± 1.257 and 3.4 ± 1.046 respectively. The results of data analysis on pain reduction using the paired t-test showed p = 0.000 (p <0.05), it means that there was a significant reduction in pain following isometric quadriceps exercise. It can be concluded that isometric quadriceps exercise can reduce pain in patients following phase I reconstruction of the ACL at Bali Royal Hospital.